Association of coffee consumption pattern and metabolic syndrome among middle-aged and older adults: A cross-sectional study - Nina, Ren; Lingling, Huang; Qiushuang, Li; Honglin, Guo; Liyuan, Sun; Yuting, Zhang (Frontiers in Public Health, 2023)
Objectives The association between coffee consumption and the risk of metabolic syndrome (MetS) remains inconsistent. The aim of this study was to evaluate the association between coffee intake and components of MetS. Method A cross-sectional survey including 1,719 adults was conducted in Guangdong, China. Data on age, gender, education level, marriage status, body mass index (BMI), current smoking and drinking status and breakfast habit, coffee consumption type, and daily servings were derived based on 2-day, 24-h recall. MetS were assessed according to the International Diabetes Federation definition. Multivariable logistic regression was conducted to examine the association between the coffee consumption type, daily servings, and the components of MetS. Results Regardless of the coffee type, compared with non-coffee consumers, coffee consumers had higher odds ratios (ORs) of the elevated fasting blood glucose (FBG) in both men [OR: 3.590; 95% confidence intervals (CI): 2.891–4.457] and women (OR: 3.590; 95% CI: 2.891–4.457). In women, the risk of elevated blood pressure (BP) was 0.553 times (OR: 0.553; 95% CI: 0.372–0.821, P = 0.004) for people who drank total coffee > 1 serving/day than for non-coffee drinkers. Conclusion In conclusion, regardless of type, coffee intake is associated with an increased prevalence of FBG in both men and women, but has a protective effect on hypertension only in women.